Supplementation with omega-3 fish oil has no effect on bone mineral density in adults with knee osteoarthritis: a 2-year randomized controlled trial. Issue 5 (May 2016) - Chen, J.; Hill, C.; Lester, S.; Ruediger, C.; Battersby, R.; Jones, G.; Cleland, L.; March, L.
Abstract Summary This study aimed to determine the effect of fish oil on bone mineral density (BMD). There were no differences in the 2-year BMD measures between high and low dose groups after adjusting for baseline BMD. This randomized controlled trial did not demonstrate any efficacy of omega-3 fatty acids on bone loss in adults. Introduction The purpose of this study is to investigate whether supplementation with high dose omega-3 fish oil could have an impact on BMD. Methods In a multicentre, double-blind randomized controlled trial (RCT) (ACTRN 12607000415404), 202 Australian participants aged ≥40 with knee osteoarthritis (mean age, 61.0 ± 10.0 years; 49 % female) were randomized to receive either high dose (4.5 g eicosapentaenoic acid and docosahexaenoic acid daily) or low dose (0.45 g/day) omega-3 fish oil for 2 years. BMD was assessed at baseline and 2 years by dual energy X-ray absorptiometry. Results In subjects with baseline and 2-year assessments, mean standardized BMD at baseline for low or high dose group was 1198 ± 198 and 1157 ± 169 mg/cm2, respectively, for the lumbar spine and was 1035 ± 165 and 1017 ± 174 mg/cm2, respectively, for the femoral neck. There were no differences in the 2-year BMD measures between high and low dose groups after adjusting for baseline BMD in the complete case regression analyses (lumbar spine 3.7, 95 % confidence interval (CI) −7.9 to 15.3 mg/cm2 and femoral neck −5.5, 95 % CI −14.9 to 3.9 mg/cm2 ). The findings did not change with additional adjustments of age, gender, study centre and uses of bone-related drugs during the study period as well as using the intention-to-treat analysis or limiting to older participants (≥55 years at the baseline) (allP ≥ 0.25). Mild adverse events such as headache and gastrointestinal intolerance were common but did not occur more frequently in either group. There were no serious adverse events related to the intervention. Conclusion A 2-year supplementation with high-dose omega-3 fish oil did not alter bone loss among men and women with knee osteoarthritis.